Exploring the big data maturity level of a metropolitan municipality in Gauteng Province, South Africa - Mathane, Tlou Phillemon (University of the Witwatersrand, Johannesburg, 2024)
A recent study by the World Bank highlights the importance of public sector organizations to embark on digital transformation. Public sector organizations that successfully undertake digital transformation journey serve their customers better; become more competitive; and improve their financial performance. Significantly, they also improve their digital maturity levels. Using a case study design, this study explored the big data maturity status quo of the Tshwane metropolitan municipality. Data maturity assessments are needful in the public sector to assist them in digital technology adoption. Conceptually, the study used the Resource View (RBV) theory to understand the extent to which this city optimizes big data as a strategic resource for decision-making. The study also used the Dynamic Capabilities Theory (DCT) to explore the extent to which big data analytics is leveraged to enhance capabilities of the city to improve service delivery. In this regard, the study focussed on five themes, viz: (a) organizational vision and strategy, (b) customer relations management, (c) data-driven- decision-making, (d) data governance, and (e) deployment of industry 4.0 best practices and/or systems. Following a qualitative design, the researcher collected data from 20 managers, using two data collection strategies. First, a focus group discussion was used to collect data from 8 managers at operational management level. A purposive sampling method was used. Secondly, structured questionnaires were administered to 12 managers, of which 6 were middle management level, and 6 were top management level incumbents. The study finds that there is no common understanding regarding the vision and strategy for digital transformation in the city. Big data analytics is not optimally used for purposes of innovation, and operational and strategic decision-making. This study contributes by uncovering some of the challenges faced by public sector organisations as far as using data to drive decision-making is concerned. In this regard, the study also tables some of the remedies and interventions that can be embarked upon to undermine some of the key teething challenges
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital transformation; Digital maturity; Smart city; Big data; Big data analytics; UCTD; SDG-8: Decent work and economic growth